Keberlangsungan Perusahaan: Lingkungan, Biaya Lingkungan dan Corporate Social Responsibility terhadap Nilai Perusahaan - Nadiatul Fauzia (Syntax Literate, 2023)
Company value has a definition that shareholders' opinions on the good and bad of a company can also be valued from the company's stock price. Shareholders assess if the higher the share price of a company, the higher the value of the company. This study aims to determine how the influence of environmental performance, environmental costs and corporate social responsibility on company value. This type of research is quantitative approach research. The data used is secondary data from company data on the Indonesia Stock Exchange that publishes annual reports and sustainability reports. The samples in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period as many as 75 samples from 25 companies using purposive sampling techniques. Based on the results of the analysis using the SPSS program version 25 for windows, it shows the results that environmental performance and environmental costs affect company value, while corporate social responsibility does not affect company value. Researchers hope that future research will not only focus on manufacturing sector companies but can expand the object of research in other sectors.